Building Social Solidarity within the Rahmatan lil 'Alamin Framework: A Sharia-Based Islamic Values Perspective - Lubna ‘Ufairoh (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the application of the values of Rahmatan lil 'Alamin in building social solidarity in modern society that faces the challenges of individualism and materialism. This study is motivated by the phenomenon of weakening empathy and cooperation in society, as well as the need to revive the value of Islamic universal affection as the basis of social harmony. Theoretical Framework: This research is based on the theory of ukhuwah insaniyyah and al-ta'awun (help-help) as the main principles of Islamic social ethics. These two concepts are a reference in understanding how the value of Rahmatan lil 'Alamin is applied practically in social, economic, and cultural life. This framework affirms that Islamic teachings are universal and emphasize the balance between human relationships with Allah (hablum minallah) and human relationships with others (hablum minannas). Literature Review: A literature review shows that the concept of Rahmatan lil 'Alamin has been widely studied in the context of da'wah, education, and humanity. However, studies that specifically highlight its relevance to social solidarity in the modern era are still limited. Some previous research has emphasized the importance of the values of compassion, social justice, and inclusivity as manifestations of the principle of rahmah in Islam, but not many have attributed it to contemporary social conditions such as social fragmentation and empathy crises. Methods: This study uses a descriptive qualitative approach with a literature study method. Data were collected from primary literature such as the Qur'an, Hadith, and books of tafsir, as well as secondary literature in the form of scientific journals, books, and contemporary research works related to social ethics and human values in Islam. The analysis was carried out thematically by interpreting the relevance of the values of Rahmatan lil 'Alamin to efforts to build social solidarity in modern society. Results: The results of the study show that the value of Rahmatan lil 'Alamin can be a foundation in strengthening social solidarity by fostering empathy, care, and social responsibility between individuals. This value also encourages tolerance between religions and cross-cultural cooperation, so as to be able to build an inclusive and just society. Its application can be carried out through Islamic character education, humanist social da'wah, and strengthening social institutions based on religious values. Implications: This study emphasizes the importance of mainstreaming Islamic spiritual values in social and educational policies to overcome dehumanization in the modern era. Novelty: The novelty of this research lies in an integrative approach that links Islamic spiritual values with contemporary social dynamics. The concept of Rahmatan lil 'Alamin is positioned not only as a moral ideal, but as a pragmatic strategy in building social solidarity and modern civilization based on the value of universal compassion.